Multi-criteria spatial-based modelling for optimal alignment of roadway by-passes in the Tlokweng planning area, Botswana. Issue 2 (4th May 2022) - Sekulic, Milan; Siljeg, Ante; Mansourian, Ali; Watson, Lisa; Cavric, Branko I.
ABSTRACT: In this study, Spatial Multi-Criteria Evaluation and the least cost path analysis were applied to find the optimal by-pass road alignment in the Tlokweng Planning Area in Botswana. One-At-a-Time sensitivity analysis and the statistical test for zero proportion were used to investigate the robustness of the entire model. Four alternative by-pass roads were produced stressing economic, environmental, and social suitability as well as trade-offs between the groups. The results showed that the social alternative performs best. Sensitivity analysis and statistical test for zero proportion revealed four criteria as sensitive.